Targeting Nrf2 with Probiotics and Postbiotics in the Treatment of Periodontitis - Karaca Basar; Yilmaz Mustafa; Gursoy Ulvi Kahraman (MDPI, 2022)
Periodontitis is a destructive disease of the tooth-surrounding tissues. Infection is the etiological cause of the disease, but its extent and severity depend on the immune-inflammatory response of the host. Immune cells use reactive oxygen species to suppress infections, and there is homeostasis between oxidative and antioxidant mechanisms during periodontal health. During periodontitis, however, increased oxidative stress triggers tissue damage, either directly by activating apoptosis and DNA damage or indirectly by activating proteolytic cascades. Periodontal treatment aims to maintain an infection and inflammation-free zone and, in some cases, regenerate lost tissues. Although mechanical disruption of the oral biofilm is an indispensable part of periodontal treatment, adjunctive measures, such as antibiotics or anti-inflammatory medications, are also frequently used, especially in patients with suppressed immune responses. Recent studies have shown that probiotics activate antioxidant mechanisms and can suppress extensive oxidative stress via their ability to activate nuclear factor erythroid 2-related factor 2 (Nrf2). The aim of this narrative review is to describe the essential role of Nrf2 in the maintenance of periodontal health and to propose possible mechanisms to restore the impaired Nrf2 response in periodontitis, with the aid of probiotic and postbiotics.